The importance of embodied energy in carbon footprint assessment. Issue 1 (8th April 2014) - Alwan, Zaid; Jones, Paul
Abstract : Purpose: – The construction industry has focused on operational and embodied energy of buildings as a way of becoming more sustainable, however, with more emphasis on the former. The purpose of this paper is to highlight the impact that embodied energy of construction materials can have on the decision making when designing buildings, and ultimately on the environment. This is an important aspect that has often been overlooked when calculating a building's carbon footprint; and its inclusion this approach presents a more holistic life cycle assessment. Design/methodology/approach: – A building project was chosen that is currently being designed; the design team for the project have been tasked by the client to make the facility exemplary in terms of its sustainability. This building has a limited construction palette; therefore the embodied energy component can be accurately calculated. The authors of this paper are also part of the design team for the building so they have full access to Building Information Modelling (BIM) models and production information. An inventory of materials was obtained for the building and embodied energy coefficients applied to assess the key building components. The total operational energy was identified using benchmarking to produce a carbon footprint for the facility. Findings: – The results indicate that while operational energy is more significant over the long term, the embodied energy of key materials should not be ignored, and is likely to be a bigger proportion of the total carbon in a low carbon building. The components with high embodied energy have also been identified. The design team have responded to this by altering the design to significantly reduce the embodied energy within these key components – and thus make the building far more sustainable in this regard. Research limitations/implications: – It may be is a challenge to create components inventories for whole buildings or for refurbishments. However, a potential future approach for is application may be to use a BIM model to simplify this process by imbedding embodied energy inventories within the software, as part of the BIM menus. Originality/value: – This case study identifies the importance of considering carbon use during the whole-life cycle of buildings, as well as highlighting the use of carbon offsetting. The paper presents an original approach to the research by using a "live" building as a case study with a focus on the embodied energy of each component of the scheme. The operational energy is also being calculated, the combined data are currently informing the design approach for the building. As part of the analysis, the building was modelled in BIM software.